2021
DOI: 10.3390/s21206723
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dynamic Positioning System with Disturbance Observer for Autonomous Marine Surface Vessels

Abstract: The main goal of the research is to design an efficient controller for a dynamic positioning system for autonomous surface ships using the backstepping technique for the case of full-state feedback in the presence of unknown external disturbances. The obtained control commands are distributed to each actuator of the overactuated vessel via unconstrained control allocation. The numerical hydrodynamic model of CyberShip I and the model of environmental disturbances are applied to simulate the operation of the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 119 publications
(137 reference statements)
0
8
0
1
Order By: Relevance
“…Taking Northern Clipper with mass of 4:591310 6 kg and length of 76:2 m as an example to simulate different situations. 22 Based on Fossen, 22 the coefficient matrices in ( 6) are taken as follows: Case 1:…”
Section: Simulation Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking Northern Clipper with mass of 4:591310 6 kg and length of 76:2 m as an example to simulate different situations. 22 Based on Fossen, 22 the coefficient matrices in ( 6) are taken as follows: Case 1:…”
Section: Simulation Examplesmentioning
confidence: 99%
“…, P 2 = 0:0217 0:0000 0:0000 0:0000 0:0217 0:0000 0:0000 0:0000 0:0116 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 1:6279310 6 0:0000 0:0000 0:0000 2:5382310 6 0:0000 0:0000 0:0000 6:2247310 8 1:7936 0:0000 0:0000 0:5979 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 1:7936 À0:0002 0:0000 0:5979 À0:0011 0:0000 0:0000 0:0000 0:0000 À0:0002 2:0340 0:0000 0:0007 1:6127 0:0000 0:0000 0:0000 0:5979 0:0000 0:0000 1:7937 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:5979 0:0007 0:0000 1:7938 0:0007 0:0000 0:0000 0:0000 0:0000 À0:0011 1:6127 0:0000 0:0007 5:5563 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0217 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0217 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0116 T , L = 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 0:0000 7:5017310 7 0:0000 0:0000 0:0000 1:1697310 8 0:0000 0:0000a 0:0000 5:3661310 10 Table 1 indicates the performance of the controlled ship at 100s. In Figures 2(a) and 3(a), it is shown that the CADC can make the ship stay in desired position (0m, 0m) and maintain a fixed attitude steadily.…”
Section: Simulation Examplesunclassified
See 1 more Smart Citation
“…Then the position and path-following control of a fully actuated autonomous underwater vehicle (AUV) was solved. An efficient controller was designed through a backstepping technique for the case of full-state feedback in the presence of unknown external disturbances, and the dynamic positioning problem for autonomous surface ships was solved in [33]. In the meantime, the obtained control commands were distributed to each actuator of the overactuated vessel via unconstrained control allocation.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, many reports of model-based path following control are limited to the simple routes (straight line [ 3 ], curved line [ 5 , 21 ], port [ 8 , 22 , 23 ] and starboard turning [ 9 , 11 ]) with an existing model presented in [ 2 , 3 , 5 , 8 , 9 , 11 , 22 , 23 , 24 ] that includes the unknown restoring forces in the dynamics. Conversely, some numerical publications [ 25 , 26 , 27 , 28 ] without experiments handle the non-diagonal matrices for sway/yaw added mass ( of 3DOF system, A26 of 6 DOF system) for practical situations based on port/starboard symmetry hull forms; however, this overlooks the nonlinear restoring terms in the dynamics, because the fast convergence and robust stability of the underactuated model considering both unknown nonlinear restoring terms and are more challenging problems. Otherwise, no specific dynamics or hydrodynamic coefficients can be seen in experiments using USV [ 29 ].…”
Section: Introductionmentioning
confidence: 99%